Optimization of PET Expression Vector for Fusion of Recombinant Protein and Elastin-Like Polypeptide Biopolymer - Mohammad Reza Soleyman; Mostafa Khalili; Alireza Soleyman Meiguni; Maryam Baazm (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2019)
Background and Aim recombinant DNA technique is a powerful and appropriate method for the production of protein biopolymers with specificity in amino acid sequence and spatial chemistry. Elastin-Like Polypeptide (ELP) is a biocompatible, biodegradable and non-immunological biopolymer used in various biotechnology studies. The ELP tag is a cheap, fast and non-chromatographic technique for purifying target proteins. In this study, pET expression vector was designed for the combination of ELP gene sequences and target recombinant protein in order to produce recombinant fusion protein with the ELP tag. Methods & Materials MOD gene was transformed to E. coli-BL21 (DE3) cells after designing and synthesis among the XbaI and XhoI restriction sites in the pET-32a (+) vector of the clone. Then, colonies were isolated based on plasmid size and examined by cutting using restriction enzymes. The final recombinant colonies was verified using polymerase chain reaction method and DNA sequencing. Ethical Considerations The Research Ethics Committee of Arak University of Medical Sciences approved all ethical considerations ofworking on laboratory animals (Code: 92-146-11). Results Replacing the MOD sequence in the pET-32a vector (+) eliminated the components expressing the fusion tags (Thioredoxin, Histidine, and S-tag), the identification site of protease enzyme (tobacco etch virus), and multiple cloning site. In addition, it added specific restriction enzyme identification sequences of ELP gene and target gene. As a result, in the optimized pET-MODvector, 466 nucleotides reduced in size and the secondary structure was improved. Conclusion Considering the improvement of spatial structure and reduction of pET-MOD vector size, as well as the possibility of the fusion of recombinant protein with the ELP tag, it is possible to use this vector for ELPyation of the target protein.